Prevalence of lymphopenia in the American population: Insights from demographic, BMI, and lifestyle factors. - Wenchi Xie; Landie Ji; Landan Kang; Qian Li; Dan Luo; Qingquan He; Jie Mei (PLoS ONE)
Objective To determine the difference in the prevalence of lymphopenia in the American population according to demographic characteristics, body mass index (BMI) and living habits. Methods A total of 33,365 participants aged over 1 were included in the 2009-2018 National Health and Nutrition Survey (NHANES). All analyses used weighted samples and considered the layering and clustering of the design. Results Using white participants as a reference, the prevalence of lymphopenia in Mexican-American participants was significantly lower than that of white participants (P = 0.018). There was no significant difference in the prevalence of lymphopenia between black participants (P = 0.376) and white participants. The prevalence of lymphopenia was 1.81% (95%CI, 1.53%-2.10%) for white participants, 1.08% (95%CI, 0.78%-1.39%) for black participants, and 0.42% (95%CI, 0.17%-0.68%) for Mexican-American participants. The prevalence of lymphopenia increases with age, reaching a peak of 6.84% among elderly participants aged 75 and above. In terms of the gender difference, the prevalence of lymphopenia in men is significantly higher than that in women (P<0.001). Individuals who smoke (P<0.001), consume alcohol (P = 0.032), engage in regular exercise (P = 0.031), have sleep disorders (P<0.001) and those classified as having an unhealthy weight (P<0.001) had a higher average lymphocyte count. The prevalence of lymphopenia in participants with sleep disorders is significantly higher than those without sleep disorders (P = 0.014). However, no significant differences were observed among the classification variables of smoking, drinking, exercise, and BMI. Conclusion In the diagnosis and treatment of lymphopenia, clinicians should consider the influence of factors such as race, gender, age, sleep disorders, and other unhealthy lifestyle habits to improve the accuracy of diagnosis and treatment, thereby reducing the high mortality risk associated with lymphopenia. Consequently, we propose a novel perspective that the diagnosis and treatment of lymphopenia should be tailored to the lymphocyte levels of specific subpopulations, rather than applying a generalized approach.